1)a²b²-4a²b²+0.25a²b²=-3a²b²+0.25a²b²=-2.75a²b<span>²
2)3m</span>²3n3k²+0.3m²k²n-5k²nm²=3m²3n3k²-4.7m²k²n
3)6pq(в 3)+4pq(в 3)+pq(в 3)=11pq(в 3)
1/3*(x^2-3)=0
x^2-3=0
x^2=3
x=√3
x=-√3
Y=2(x^2+6x+9)-1
y=2x^2+12+17
x=-b/2a
x=-12/4=-3
(1/2)^log(2)(x²-1)>1
ОДЗ х²-1>0⇒x∉(-∞;-1) U (1;∞)
2^log(2)1/(x²-1)>1
1/(x²-1)>2
1/(x²-1)-2>0
(1-2x²+2)/(1-x²)>0
(3-2x²)/(x²-1)>0
(√3-√2x)(√3+√2x)/(x-1)(x+1)>0
x=√6/2 x=-√6/2 x=1 x=-1
_ + _ + _
________________________________________________
-√6/2 -1 1 √6/2
x∈(-√/2;-1) U (1;√6/2)